Overview of integrated reporting: biliometric analysis - Nguyet Phan Minh; Tuan Le Anh; Hai Phan Thanh; Nhi Vo Van (Cogent Business & Management)
This study aims to provide broad information on integrated reporting, including authors, journals, countries and references. Using Scopus data source from 2012 to 2024 with 468 studies on integrated reports for bibliometric analysis with the support of VOS viewer software version 1.6.20. The results show that there are not many studies addressing IR, especially in developing countries, but only focus on a few large economies. Some research characteristics related to the topic of IR have also been pointed out such as the main type of documents are scientific articles (94%), some journals from reputable publishers have a large number of publications, the research fields related to IR are still business, management and accounting (93.8%). In addition, after using the techniques, there are 05 research directions that have been implemented related to integrated reporting: (1) Research on financial statements based on the aspects of capital costs and enterprise value, voluntary disclosure; (2) Research on financial statements based on agency theory, board of directors and financial statement disclosure risk; (3) Research on financial statements based on stakeholder theory and enterprise performance; (4) Research on financial statements based on financial statement templates and non-financial information; (5) Research on financial statements based on materiality and stakeholders. From there, it opens up future research expectations. However, this study only uses data sources from Scopus, so the analysis results may not cover all published studies. Further studies can add data from other sources to increase the objectivity of the research results.